The Impact of Teachers’ Professional Development on EFL Learners’ Performance The Case Study of Teachers in the Department of English at the University of Laghouat - Ferdi ,Hassiba; Horri, Zineb Elghazali; Gasmi Mustapha (Faculty of Letters and Foreign Languages Department of English, 2017)
Many people may not be aware of their educational system‘s methods for improving teaching and student learning. Professional development is the most important strategy educational systems have to strengthen educators‘ performance levels. It is also the only way educators can learn so that they are able to better their performance and raise student achievement. Teachers want and need to develop their practice so that their students can succeed. In most places, these fall under the auspices of professional development. In this study, we use descriptive research as an appropriate procedure to achieve this work. The study describes the influence of Teachers‘ professional development on learners‘ performance. The quantitative approach is also used for collecting data through questionnaire administered for teachers. All data obtained from the questionnaire are analyzed, interpreted and represented in form of figures and tables. In conclusion, we present some findings of the study, one of them is the appropriate staff development‗s modes that promote teachers‘ knowledge and skills to raise students‘ achievement